1991
DOI: 10.1111/j.1151-2916.1991.tb04302.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability and Physical Properties of Cubic and Tetragonal ZrO2 in the System ZrO2–Y2O3–Ta2O5

Abstract: The cubic (c-ZrO,) and tetragonal zirconia (t-ZrO,) phase stability regions in the system ZrO2-Y2O3-Ta2O5 were delineated. The c-Zr02 solid solutions are formed with the fluorite structure. The t-ZrO, solid solutions having a c/u axial ratio (tetragonality) smaller than 1.0203 display high fracture toughness (5 to 14 MPa-m"'), and their instability/ transformability to monoclinic zirconia (m-ZrO,) increases with increasing tetragonality. On the other hand, the t-ZrO, solid solutions stabilized at room temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(45 citation statements)
references
References 10 publications
6
39
0
Order By: Relevance
“…In particular, these compositions are phase stable at 1500°C and particularly resistant to sulfate/vanadate corrosion [7]. Moreover, they exhibit very high levels of tetragonality which results in indentation fracture toughness values comparable or higher than 7YSZ [8,9].…”
Section: Introductionmentioning
confidence: 96%
“…In particular, these compositions are phase stable at 1500°C and particularly resistant to sulfate/vanadate corrosion [7]. Moreover, they exhibit very high levels of tetragonality which results in indentation fracture toughness values comparable or higher than 7YSZ [8,9].…”
Section: Introductionmentioning
confidence: 96%
“…Any excess is accommodated by a second phase, either YTa3O9 or Y3TaO7. Based on the diagram by Kim and Tien, [2] and the more recent work of Pitek and Levi, [5] the tentative phase diagram at 1500 o C that has guided our studies is shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…As part of this search, the zirconia-rich portion of the Y-Ta-Zr-O system has been investigated. The basic features of the zirconia-rich portion of the phase diagram were described by Kim and Tien, [2] with an emphasis on the stability of the tetragonal and cubic phases. More recently, in a series of papers, Levi and colleagues have elaborated on the phase stabilities in the zirconia-rich portion of the phase diagram, more clearly delineating the phase fields and relating some of the physical properties such as fracture toughness and thermal conductivity to the phase content.…”
Section: Introductionmentioning
confidence: 99%
“…In this context the tetragonal form of zirconia attracts much attention because it is the martensitic transformation from metastable tetragonal to monoclinic zirconia under applied stresses that gives rise to transformation toughening (Green et al 1988). Tetragonal zirconia alloys in ternary oxide systems have been the subject of several studies aimed at understanding the factors influencing the stability of the tetragonal phase (Kim et al 1993;Kim and Tien 1991;Kim 1990;Lin et al 1990;Pydra et al 1991;Wilson and Glasser 1989;Li et al 1994).…”
Section: Introductionmentioning
confidence: 99%